Uma Casa no Limiar da Cidade: projeto de reabilitação em Penafiel - Mariana da Silva Ribeiro (2020)
The achievement of this last phase of the course came from a personal concern, related to the permanence of the land in which I lived and grew. Time goes by and it takes with it what it once was, which is no longer, but it wants to be again. We are heading in a direction without return, but certainly hoping to preserve and refine what stands out in the history of our cities, in unison with the evolution that accompanies us. Therefore, the desire arises to develop an intervention porposal in a single family habitation that, besides its large spatial dimension and its voluminous façade, presents itself on the edge of the city. This peculiarity drags on a complex theme that includes the rural / urban dialectic. This dissertation covers an entire process of detailed survey of the building and a rehabilitation proposal that reflects on the importance of the pre-existing and on the circumstances surrounding it, as well as on the imposition of several conditions underlying the intervention that, in this way, clarify the theoretical research carried out. The work aims to articulate and boost the urban, tourist and agricultural potential of the space, in order to make the investments profitable and consolidate the prospects for the future.